Inequalities in Malaysia: editorial cartoon / Muhammad Amirun Hanif Zulkifli - Zulkifli, Muhammad Amirun Hanif (Faculty of Art and Design, 2020)
Editorial cartoon are cartoons that have massages or issues that are bought to the people.